Epidemiology of Polypharmacy and Potential Drug–Drug Interactions Among Pediatric Patients in ICUs of U.S. Children's Hospitals*. Issue 5 (May 2016) - Dai, Dingwei; Feinstein, James A.; Morrison, Wynne; Zuppa, Athena F.; Feudtner, Chris
Abstract : Objectives: Polypharmacy is common in hospitalized children in the United States and has been identified as a major risk factor for exposure to potential drug–drug interactions. Little is known about the characteristics and prevalence of exposure of pediatric patients to polypharmacy and potential drug–drug interactions in PICUs. Design: Retrospective cohort study using the Pediatric Health Information System database. Setting: Forty-two freestanding children's hospitals throughout the United States. Patients: A total of 54, 549 patients less than 18 years old cared for in PICUs in 2011. Patients in neonatal ICUs were not included. Measurements and Main Results: PICU patients were on average exposed to 10 distinct drugs each hospital day and to 20 drugs cumulatively during their hospitalization. Seventy-five percent of patients were exposed to greater than or equal to one potential drug–drug interaction regardless of severity level, 6% to greater than or equal to one contraindicated potential drug–drug interaction, 69% to greater than or equal to one major potential drug–drug interaction, 57% to greater than or equal to one moderate potential drug–drug interaction, 19% to greater than or equal to one minor potential drug–drug interaction. Potential drug–drug interaction exposures were significantly associated with specific diagnoses ( p < 0.001), presence of complex chronic conditions ( p < 0.001), increasing number of total distinct drugs used ( p < 0.001), increasing length of stay in PICU ( p < 0.001), and white race ( p < 0.001). Conclusions: Many PICU patients are exposed to substantial polypharmacy and potential drug–drug interactions. Future research should identify the risk of adverse drug events following specific potential drug–drug interaction exposures, especially the risk of adverse drug events due to multiple potential drug–drug interaction exposures, and determine the probability and magnitude of the actual harm (if any) for each specific potential drug–drug interaction, especially for multiple potential drug–drug interaction exposures. Abstract : Supplemental Digital Content is available in the text.